Palavra e imagem : diálogo entre as linguagens literária e fílmica - Spuldaro, Daiane Casagrande (2009)
The reasons that took to the accomplishment of this study appeared of the interest and of the need to investigate some experiences related to the adaptation of the literary for the cinematographic, approaches and/or modifications of the book that originated the film, starting from the new cultural formulations of behaviors and point of view of a world that it is in constant mutation. For the development of this descriptive qualitative research, which considered the participation of the people as one of the elements of yours to do scientific, it was necessary a theoretical research addressed to the literary language and filmic language, to the relationship of the works with the reader/viewer, to the constitution of the narrative structures and convergence aspects and divergence among those two artistic manifestations. In the practice, a group was formed with volunteers with the objective of reading the literary works and, subsequently, watch its adaptation, for orientate a reflection concerning the languages present in the verbal and filmic narratives, because so much the literature as the movies have the eyes of the receiver as starting point for the constitution of its existence. The selected works were: Desmundo, romance of Ana Miranda (1996), adapted for the movies in 2003, for Alain Fresnot; O amor nos tempos do cólera, romance of Gabriel Garcia Márquez (1985), transposed for the movies in 2007, by Mike Newell; and the poem "Caso do vestido", of Carlos Drummond de Andrade (1945), adapted in 2004 for the movies, by Paulo Thiago. In a different way, the personal interpretations of each individual happened starting from the interaction with the book and with the film, result of its previous knowledge about gender, the form and the thematic of the works already know/read, and of the opposition among the two supports. The analyses didn't limit to the aesthetic aspects and you structure of the works, because in the reading and in the interpretation also entered in angle the personal experiences, because among the reception of a work and the intended effect, it happens the process of the understanding, demanding all accumulated knowledge from the reader